SEARCH FOR OLD PRINTS BY VACLOVAS BIRŽIŠKA, DIRECTOR OF THE LIBRARY OF VYTAUTAS MAGNUS UNIVERSITY, IN SAMOGITIA - PETREIKIS, TOMAS (Knygotyra, 2012)
In independent Lithuania, no legal framework for the protection of the press and manuscript heritage had been created, neither had the state a targeted strategy for its protection; therefore, only the public initiative in this area provided considerable results on the public grounds, by creating museums and libraries in province. The attention of V. Biržiška, Director of the library of Vytautas Magnus University (VMU) and the Institute of Lithuanian Bibliography, towards the press heritage could be characterized by single-mindedness. By shaping the University library funds, he tried to gather there the heritage of the old Lithuanian press and manuscripts as much as possible, as it could provide an appropriate framework for the further research in Lithuanian philology. In a systematic manner V. Biržiška had been using the help of Lithuanian educators and students in the search of the press heritage since 1924. In Samogitia, he kept in touch with educators from Šiauliai and Telšiai. In Telšiai, he received some publications from Viktoras Kamantauskas, the local gymnasium teacher, and doctor Jonas Mikulskis. The library was significantly supported also by the Šiauliai State Gymnasium, which within a few years gave more than four thousand publications to the library. For eight years Jonas A. Dargis from the Barstyčiai town had been collecting and supplying old books to V. Biržiška. He mostly acted in Northern and Western Samogitia. Within less than a decade, the funds of the VMU library had been supplemented by approximately four and a half thousand publications from Samogitia, among them several quite unique. The active search of the press heritage by V. Biržiška drew public attention to old books and caused an increase of their price, which in turn determined the subsequent movement of bibliophilia.
Keywords: ...